Меѓузависноста на буџетскиот дефицит, јавниот долг и фискалната одржливост - Ташевска, Билјана (Економски факултет, УКИМ, Скопје, 2015)
The global economic crisis and the debt crisis in the Eurozone reemphasized the importance of sustainable public finances. The crisis first showed the need for fiscal intervention and fiscal activism, but then brutally proved the need for fiscal authorities to balance between the short term stabilization goals of fiscal policy and the long term fiscal sustainability. The rapid buildup of public debt in an environment of low growth and financial instability and its severe consequences increased the interest of economists for this problem. This doctoral dissertation contributes to the large number of studies of focused on the consequences of a large and ever increasing amount of public debt. It aims at creating a complete picture of the interdependence of budget deficits, public debt and fiscal sustainability. This provides a basis for the analysis of the fiscal policy of the Republic of Macedonia and for an empirical assessment of its sustainability, which is in the main focus of the research, aimed at detecting the possible need for a fiscal adjustment.
The interdependence of budget defficit, public debt and fiscal sustainability
Докторска дисертација одбранета во 2015 година на Економскиот факултет во Скопје, под менторство на проф. д–р Таки Фити.
Keywords: fiscal policy, budget deficit, public debt, primary budget balance, fiscal sustainability, fiscal consolidation